Neuroethics beyond Normal: Performance Enablement and Self-Transformative Technologies - Shook, John R. (Cambridge quarterly of healthcare ethics, 2016)
An integrated and principled neuroethics offers ethical guidelines able to transcend conventional and medical reliance on normality standards. Elsewhere we have proposed four principles for wise guidance on human transformations. Principles like these are already urgently needed, as bio- and cyberenhancements are rapidly emerging. Context matters. Neither “treatments” nor “enhancements” are objectively identifiable apart from performance expectations, social contexts, and civic orders. Lessons learned from disability studies about enablement and inclusion suggest a fresh way to categorize modifications to the body and its performance. The term “enhancement” should be broken apart to permit recognition of enablements and augmentations, and kinds of radical augmentation for specialized performance. Augmentations affecting the self, self-worth, and self-identity of persons require heightened ethical scrutiny. Reversibility becomes the core problem, not the easy answer, as augmented persons may not cooperate with either decommissioning or displacement into unaccommodating societies. We conclude by indicating how our four principles of self-creativity, nonobsolescence, empowerment, and citizenship establish a neuroethics beyond normal that is better prepared for a future in which humans and their societies are going so far beyond normal.